2010
DOI: 10.1016/j.eurpsy.2009.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of psychotic features on morbidity and course of illness in patients with bipolar disorder

Abstract: The well identified psychotic subtype of bipolar patients may give important predictions about long term course and prophylaxis of bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 25 publications
1
15
1
1
Order By: Relevance
“…Additionally, the smaller number of psychotic participants limited the power of comparisons within this subgroup. In contrast to these results, Ozyildirim et al found that bipolar participants were more likely to respond to lithium when psychosis was not present (Ozyildirim et al, 2010). However, this study differed from the current study in that included only BD-I patients, pooled results of all mood episodes, and compared patients with psychosis in all episodes with those who had never experienced psychosis rather than those who were not currently experiencing it.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Additionally, the smaller number of psychotic participants limited the power of comparisons within this subgroup. In contrast to these results, Ozyildirim et al found that bipolar participants were more likely to respond to lithium when psychosis was not present (Ozyildirim et al, 2010). However, this study differed from the current study in that included only BD-I patients, pooled results of all mood episodes, and compared patients with psychosis in all episodes with those who had never experienced psychosis rather than those who were not currently experiencing it.…”
Section: Discussioncontrasting
confidence: 92%
“…associated with reduced recovery rates (Solomon et al, 2010), shorter time to first recurrence (Pallaskorpi et al, 2015;Tohen et al, 2003b), more hospitalizations (Mazzarini et al, 2010;Ozyildirim, Cakir, & Yazici, 2010), and neurocognitive deficits (Tsitsipa & Fountoulakis, 2015).…”
mentioning
confidence: 99%
“…Psychotic symptoms in BD are predictive of a more detrimental course, including a higher rate of rehospitalizations (Caetano et al, 2006; Ozyildirim et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Of note, more than half of the bipolar patients have hallucinations and delusions at least once during a mood episode [2], and patients with major depressive disorder (MDD) may present psychotic symptoms in 19-25% of cases [3] with worse outcomes than patients without psychotic symptoms [4]. The identification of biological markers (e.g.…”
Section: Introductionmentioning
confidence: 99%